2015
DOI: 10.1111/ijsa.12115
|View full text |Cite
|
Sign up to set email alerts
|

Applicant Anxiety: Examining the sex‐linked anxiety coping theory in job interview contexts

Abstract: The Sex-linked Anxiety Coping Theory (SCT) suggests that anxiety should relate to performance more strongly for males than females. In Study 1, we examined how the theory applied to five interview anxiety dimensions (appearance anxiety, behavioral anxiety, communication anxiety, performance anxiety, and social anxiety) using actual job applicants. In general, females reported higher levels of each type of interview anxiety than did males. However, consistent with SCT, Overall Interview Anxiety, Appearance Anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 53 publications
4
22
0
Order By: Relevance
“…Third, experience tends to increase with age, making age an important control variable. And fourth, gender differences tend to be frequently observed in anxiety research (see also Boyer et al, 2017;Egloff and Schmukle, 2004;Feeney et al, 2015;Zalta and Chambless, 2012), if not always (see Feiler and Powell, 2013). Interview experience was measured with the help of three newly developed items.…”
Section: Methodsmentioning
confidence: 99%
“…Third, experience tends to increase with age, making age an important control variable. And fourth, gender differences tend to be frequently observed in anxiety research (see also Boyer et al, 2017;Egloff and Schmukle, 2004;Feeney et al, 2015;Zalta and Chambless, 2012), if not always (see Feiler and Powell, 2013). Interview experience was measured with the help of three newly developed items.…”
Section: Methodsmentioning
confidence: 99%
“…More research is also needed about potential consequences on applicants' reactions, for instance perceptions of interpersonal treatment (e.g., Gilliland & Steiner, ). Warnings could make candidates feel more uncomfortable, which may negatively impact their ability to perform (Feeney, McCarthy, & Goffin, ). Warnings combined with announcements of negative consequences for those who are caught lying could also backfire and damage the recruitment function of the interview.…”
Section: What Are the Antecedents Of Faking In Interviews?mentioning
confidence: 99%
“…For undergraduates, the latter stage of the recruitment process, the job interview, is an alien and anxiety-provoking environment (Wittmann- Price, Price, Graham & Wilson, 2016). Interviews are high pressure situations that often produce undesirable behavioural 'slips' (e.g., stuttering and memory 'blanks') due to anxiety (Feeney, McCarthy & Goffin, 2015). Yet, there is little information in the pedagogical literature on how to explicitly prepare undergraduates for this inevitable experience, particularly in the field of sport; something this paper aims to address.…”
Section: Graduate Job Interviewsmentioning
confidence: 99%
“…For example: Participants indicated that the ways in which the interviews were set-up presented a relatively safe space to make mistakes. They felt it was a useful learning space and there was evidence in the focus group discussions that experiential learning processes had allowed them to learn come coping techniques for overcoming interview-based anxiety often experienced by (under)graduates in job interviews (Feeney et al, 2015 In addition, in and through this learning space, academic staff who acted as the interview panel were often viewed as critical friends rather than assessors. Students felt the feedback they received from this activity was meaningful and constructive, perhaps more so than other feedback they'd had.…”
Section: Mock Job Interviews As An Assessment Mode: Benefits and Chalmentioning
confidence: 99%